1993
DOI: 10.1007/bf02641886
|View full text |Cite
|
Sign up to set email alerts
|

Total occlusion of iliac arteries: Results of balloon angioplasty

Abstract: Fifty-six occluded iliac arteries (mean length 6.1 cm; range 1-17 cm) in 50 patients were treated by percutaneous transluminal angioplasty (PTA) or laser-assisted PTA (bilateral lesions in 6 patients). Twenty-seven patients (54%) were at high risk for surgery. Patients were followed for a maximum period of 72 months (mean 23.12 months; median 20 months). The initial success rate was 78.57% for arteries and 82% for patients. Laser-assisted PTA was attempted in 11 occluded arteries (19.64%) and was successful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 41 publications
0
18
0
3
Order By: Relevance
“…Failure rates for iliac and femoropopliteal CTO are 3% to 36% [25][26][27][28][29][30][31][32][33] and 12% to 25%, 34,35 respectively. Novel alternative devices and techniques have had varied success for coronary and peripheral artery CTO recanalization, although to date none have prevailed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Failure rates for iliac and femoropopliteal CTO are 3% to 36% [25][26][27][28][29][30][31][32][33] and 12% to 25%, 34,35 respectively. Novel alternative devices and techniques have had varied success for coronary and peripheral artery CTO recanalization, although to date none have prevailed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The recanalization of the iliac occlusions is still debated, even though it reached a primary technical success in the percutaneous approach to iliac occlusions with PTA plus stenting close to 80% (9,13,14). Vorwerk et al, without performing the thrombolysis, reported a success in 81% of cases in terms of passing through the occlusion (9).…”
Section: Discussionmentioning
confidence: 99%
“…The primary patency rate at 1 year after PTA of iliac arteries ranges between 77% and 96%. [1][2][3][4][5] For PTA of femero-popliteal arteries the reported 1 year primary patency rates are lower at 42-76%. 4,6 -10 Additional stent implantation improves these results in the iliac arteries to 87-98%, [11][12][13][14][15][16][17] however, in femoro-popliteal arteries stent placement results in no long-term improvement with 1 year primary patency rates of 22-81%.…”
mentioning
confidence: 99%